Thermal Load Application Method for Temperature Cycle Test of Power Module PP-IGBT - Biaojun LI; Mei LENG; Jiashui DAI; Ning WANG (Zhongguo dianli)
Temperature cycling test is an important test method to study the thermal fatigue aging characteristics of power module press pack insulated gate bipolar transistor (PP-IGBT) devices. Therefore, taking the PP-IGBT of flexible direct converter valve power module as the research object, and combined with theoretical calculation and finite element simulation analysis, a thermal load application method for temperature cycle test is proposed, and the corresponding electrical input target parameters are obtained. A temperature cycle test platform is built to monitor the device temperature in real time, and a comprehensive comparison analysis is made on the temperature data of the junction, shell and heatsink at the measuring point of the tested power module IGBT devices. The simulation results have verified the effectiveness of the proposed method, and can provide a research approach for the PP-IGBT test of the same type.